Connective Action and Meaning Formation in the Digital Era: A Case Study of the #Alleyesonpapua Campaign - Kamaratih Purnama Kusuma; Agnes Yusuf; Siti Maharani Nabilah; Sintya Chalifia Azizah; Lucky Alfa Riztri (Green Publisher Indonesia, 2025)
This study examines #AllEyesonPapua digital campaigns as a form of connective action in digital activism that develops organically through social media. This research uses a qualitative approach with interpretive paradigms and case studies to understand how meaning, collective emotions, and digital solidarity are formed in the digital space. Using the perspective of Social Construction of Technology (KST), this study emphasizes that social media is not neutral but rather a social space full of negotiation of meaning and power. Data were collected through in-depth interviews with informants who were actively involved in #AllEyesonPapua campaign interactions in the digital space and analyzed using thematic coding techniques. The results show that #AllEyesonPapua campaigns form digital solidarity through personalized narratives, evocative visual symbols, and strong emotional resonances. Social media acts as an affective space that allows for the expression of collective emotions and the articulation of meaning broadly. The findings also reveal that this campaign faces challenges in the form of stigmatization, digital attacks, and limited access to votes from directly affected communities.